Impacts of concurrent cigarettes and e-cigarettes use on university students’ psychological well-being, health, and smoking cessation - Elsaieh, Wali Afaf Masaud (2024)
Smokers of e-cigarettes and traditional tobacco cigarettes are 2.6 times more likely to develop lung disease than non-smokers, with dual cigarette use rapidly increasing over the last decade. This rise in dual cigarette use has significantly raised the risk of lung disease among Malaysian adults. To address this public health concern, this study investigates the variables influencing dual cigarette use among adults, with a particular focus on higher education institutions. Specifically, it explores the relationship between socio-demographic factors and the smoking status of single and dual cigarette users. Additionally, the study examines potential differences in nicotine dependence, smoking habits, and willingness to quit smoking between these groups. The impact of demographic factors on the psychological well-being and smoking cessation efforts of Malaysia’s younger population is also emphasized. Data were collected through a cross-sectional survey involving 386 students across four specified higher education institutions. The data were analyzed using SPSS version 25, employing statistical tests such as the Chi-square test of independence, Mann-Whitney U test, and Kruskal Wallis test. The results indicate that, except for gender (ꭓ2=6.036, p =0.049), there is no significant relationship between five socio-demographic factors (gender, age, ethnicity, CGPA, and parents’ income) and students’ smoking status. Regarding nicotine dependency, single users exhibit a slightly higher mean score (9.27 ± 7.97) compared to dual users (8.24 ± 4.67), with a Mann-Whitney U test p-value of 0.045, indicating a statistically significant difference. However, there was no significant difference in smoking practices between single users (3.89 ± 0.89) and dual users (3.95 ± 0.82), with a p-value of 0.628. Similarly, perceptions of health risks and psychological well-being also show no significant differences (p > 0.05) between these groups (3.76 ± 0.90 for single users) and dual users (3.82 ± 0.95). In assessing the willingness to quit smoking among three groups (single-cigarette users, single-vape users, and dual users), the study found no statistically significant differences in nicotine dependency, smoking practices, perceptions of health risks, or psychological well-being (p > 0.05). The study concludes by presenting a framework for addressing health risks associated with dual tobacco and e-cigarette use, focusing on smoking habits, nicotine dependency, and socio-demographic factors. This framework was evaluated by a panel of experts against criteria such as clarity, reliability, applicability, completeness, and sustainability. These findings can guide higher education authorities in developing effective smoking cessation programs tailored to the smoking status of students, with a particular emphasis on supporting single smokers who demonstrate a higher inclination to quit compared to dual smokers.